The Double Sumudu-Sawi Transform (European Journal of Pure and Applied Mathematics, 2025)
The paper explores integral transforms and their broader generalizations. The primary aim is to develop a new integral transform that combines the Hybrid Sumudu and Sawi transforms, investigating their properties, existence, and inversion theorem. We introduce recent findings on partial differential equations in higher dimensions and broaden the scope of the double convolution theorem to encompass two-dimensional scenarios. Utilizing these novel properties and theorems, we solve particular types of differential equations, showcasing their practical applications in physics and various scientific domains.
Keywords: Sumudu transform; Sawi transform; The Double Sumudu-Sawi transform